Determination of physicochemical quality parameters of fruit wines produced in Republic of Serbia - Čakar, Uroš; Stanković, Ivan; Djordjević, Brižita (Archives of Pharmacy, 2024)
Fruit wines are products obtained after the processing of fruit crops which are not grapes. Water and alcohol are the most abundant constituents of fruit wines, along with biologically active compounds which are present in small amounts. Taken together, they significantly affect the physicochemical quality parameters. Before market placement, it is important to determine the physicochemical quality parameters of fruit wines. This study deals with the determination of physicochemical quality parameters in blackberry and sour cherry fruit wines produced in Serbia. The total content of acids determined by titration was in the interval from 7.37 to 9.05 g/L express to mallic acid. The pH values were from 2.75 to 3.57. The content of free SO2 is important to prevent spoilage induced by microorganisms, and it was in the range from 12.52 to 15.21 mg/L. The ethanol content of samples was in the interval from 6.87 to 13.57 % v/v. The obtained values for ethanol content were in accordance with the initial content of sugar in vinification, which was in the range from 13.8 to 24.2 ° Brix. Total phenolic content of fruit wines was from 1895.77 to 2417.21 mg/L expressed as gallic acid equivalents. All the investigated physicochemical parameters of the analyzed fruit wines, except ethanol content, were in line with the National Regulations for Quality and Other Demands for Grape Wine (National Regulations). The obtained results indicate the quality of fruit and demonstrate that all the procedures applied during wine production were conducted properly to obtain a quality final product. Ethanol content was below the minimal limit in 5 of 11 analyzed samples according to the National Regulations. This can be explained by the fact that every fruit has a different composition of natural constituents, which is a crucial reason to adopt specific regulations related to quality and other requirements for fruit wines.